Advanced Glycation End Products and Bone Metabolism in Patients with Chronic Kidney Disease - Quadros, Kélcia R. S.; Roza, Noemi A. V.; França, Renata A.; Esteves, André B. A.; Barreto, Joaquim; Dominguez, Wagner V.; Furukawa, Luzia N. S.; Caramori, Jacqueline Teixeira [UNESP]; Sposito, Andrei C.; de Oliveira, Rodrigo Bueno (Oxford University Press (OUP), 2023)
Advanced glycation end products (AGEs) accumulation may be involved in the progression of CKD-bone disorders. We sought to determine the relationship between AGEs measured in the blood, skin, and bone with histomorphometry parameters, bone protein, gene expression, and serum biomarkers of bone metabolism in patients with CKD stages 3 to 5D patients. Serum levels of AGEs were estimated by pentosidine, glycated hemoglobin (A1c), and N-carboxymethyl lysine (CML). The accumulation of AGEs in the skin was estimated from skin autofluorescence (SAF). Bone AGEs accumulation and multiligand receptor for AGEs (RAGEs) expression were evaluated by immunohistochemistry; bone samples were used to evaluate protein and gene expression and histomorphometric analysis. Data are from 86 patients (age: 51 ± 13 years; 60 [70%] on dialysis). Median serum levels of pentosidine, CML, A1c, and SAF were 71.6 pmol/mL, 15.2 ng/mL, 5.4%, and 3.05 arbitrary units, respectively. AGEs covered 3.92% of trabecular bone and 5.42% of the cortical bone surface, whereas RAGEs were expressed in 0.7% and 0.83% of trabecular and cortical bone surfaces, respectively. AGEs accumulation in bone was inversely related to serum receptor activator of NF-κB ligand/parathyroid hormone (PTH) ratio (R = −0.25; p = 0.03), and RAGE expression was negatively related to serum tartrate-resistant acid phosphatase-5b/PTH (R = −0.31; p = 0.01). Patients with higher AGEs accumulation presented decreased bone protein expression (sclerostin [1.96 (0.11–40.3) vs. 89.3 (2.88–401) ng/mg; p = 0.004]; Dickkopf-related protein 1 [0.064 (0.03–0.46) vs. 1.36 (0.39–5.87) ng/mg; p = 0.0001]; FGF-23 [1.07 (0.4–32.6) vs. 44.1 (6–162) ng/mg; p = 0.01]; and osteoprotegerin [0.16 (0.08–2.4) vs. 6.5 (1.1–23.7) ng/mg; p = 0.001]), upregulation of the p53 gene, and downregulation of Dickkopf-1 gene expression. Patients with high serum A1c levels presented greater cortical porosity and Mlt and reduced osteoblast surface/bone surface, eroded surface/bone surface, osteoclast surface/bone surface, mineral apposition rate, and adjusted area. Cortical thickness was negatively correlated with serum A1c (R = −0.28; p = 0.02) and pentosidine levels (R = −0.27; p = 0.02). AGEs accumulation in the bone of CKD patients was related to decreased bone protein expression, gene expression changes, and increased skeletal resistance to PTH; A1c and pentosidine levels were related to decreased cortical thickness; and A1c levels were related to increased cortical porosity and Mlt. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.
Keywords: ADVANCED GLYCATION END PRODUCTS; BONE METABOLISM; CHRONIC KIDNEY DISEASE